Correlations between unconfined compressive strength, sorptivity and pore structures for geopolymer based on SEM and MIP measurements. (15th May 2023) - Zhu, Zhiduo; Huo, Wangwen; Sun, He; Ma, Borui; Yang, Liu
Abstract: The objective for this research was to investigated the unconfined compressive strength, sorptivity, pore structures and their correlations of recycled concrete fine powder (RCFP) based geopolymers mixed with different granulated blast furnace slag (GBFS). The unconfined compressive strength and sorptivity tests were utilized to measure the unconfined compressive strength and sorptivity coefficient. The pore structures were analyzed using optical method (SEM) and mercury intrusion method (MIP). The particles (pores) and cracks analysis system (PCAS) and image-pro plus (IPP) software were employed to quantitatively characterize the multi-scale micropores in the SEM images. Furthermore, based on MIP measurement and two fractal theories, the variations in pore structural characteristics were evaluated. The findings demonstrate the incorporation of GBFS effectively reduced the sorptivity coefficient and enhanced the unconfined compressive strength, and this effect grew stronger with increasing content of GBFS. The sorptivity coefficient and 28-day unconfined compressive strength had a strong linear negative connection. According to SEM analysis, increasing GBFS facilitated the generation of that greater number of gelling products by improving the degree of reaction, which led to a refinement of internal pore structure and an increase in structural complexity. Meanwhile, the addition of GBFS and increasing its content could effectively facilitate the conversion of macropores into micropores by filling with gel products, and significantly reduce the porosity, threshold pore size and most probable pore size. The unconfined compressive strength and sorptivity coefficient had good linear relationships with its internal porosity. The pore structures of geopolymers had clear fractal features as a whole. Among the two models, the thermodynamic model was more suitable to evaluate the fractal characteristic of the pores for geopolymer. The unconfined compressive strength rose with increasing surface fractal dimension, while the sorptivity coefficent exhibited an opposite trend. Graphical abstract: Image 1 Highlights: The relationships between pore structures and engineering properties of geopolymer were estimated. The evolution of unconfined compressive strength and sorptivity coefficient at different GBFS contents was clarified. The formation mechanism of geopolymer microstructure and its influence on macroscopic properties were revealed.